2017
DOI: 10.1051/matecconf/201713305001
|View full text |Cite
|
Sign up to set email alerts
|

Stress analysis of a link for slat chain conveyor

Abstract: Abstract. This paper analyzes stresses in a link of a slat chain conveyor loaded with rock mass. Tensometric data and results from numerical simulation with Finite Element Method (FEM) are used. The tensometric measurements are performed in real life conditions. For numerical simulation an adequate model with FEM has been created. The adequacy of the model is confirmed by the comparison of the experimental and numerical results. The factor of safety used in the design of the conveyor links is determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Li et al 14 adopted multi-body dynamic technology to establish a dynamic model of a new sprocket drive mechanism, and accurately simulated the meshing process of roller chain drive. Veselin et al 15 used the finite element numerical simulation method to analyze the stress of the scraper conveyor, and verified the correctness of the model through experiments. Lu et al 16 proposed a compound sliding mode control method based on the permanent magnet direct drive system to realize the smooth start of the scraper conveyor.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 14 adopted multi-body dynamic technology to establish a dynamic model of a new sprocket drive mechanism, and accurately simulated the meshing process of roller chain drive. Veselin et al 15 used the finite element numerical simulation method to analyze the stress of the scraper conveyor, and verified the correctness of the model through experiments. Lu et al 16 proposed a compound sliding mode control method based on the permanent magnet direct drive system to realize the smooth start of the scraper conveyor.…”
Section: Introductionmentioning
confidence: 99%
“…However, not many studies have been found on slat or chain conveyors specifically [17], nor on the stress-strain analyses of their crossbars, while no literature dealing with the bending deformation of the slat conveyor crossbars due to the thermal-mechanical loading was found. The most related study, dealing with the stress-strain analysis of slat conveyors, was the study of Tsonev [18], where an FE analysis of a chain link of a slat conveyor for rock material transportation was performed to identify the reasons for its destruction. Here, the FE model of the chain link was verified by experimental stress measurements.…”
Section: Introductionmentioning
confidence: 99%